Humanocracy creating organizations as amazing as the people inside them - Gary Hamel and Michele Zanini (Boston, MA Harvard Business Review Press, 2020)
"Our organizations are failing us. They're sluggish, change-phobic, and emotionally arid. Human beings, by contrast, are adaptable, creative, and full of passion. This gap between individual and organizational capability is the unfortunate by-product of bureaucracy--the top-down, rule-choked management structure that undergirds virtually every organization on the planet. Invented in the nineteenth century with the goal of turning people into semi-programmable robots, bureaucracy is deeply dehumanizing. Today, only 13 percent of employees around the world are fully engaged in their work. The rest show up physically but leave much of their enthusiasm and ingenuity at home--hardly surprising given the tendency of bureaucrats to regard human beings as mere "resources." By the authors' reckoning, bureaucracy costs the global economy more than
Includes bibliographical references and index.
Keywords: Bureaucracy